Academic buoyancy, student's achievement, and the linking role of control: A cross‐lagged analysis of high school students. (21st January 2015) - Collie, Rebecca J.; Martin, Andrew J.; Malmberg, Lars‐Erik; Hall, James; Ginns, Paul
<x xml:space="preserve">Abstract</x> Background Previous research has indicated that although academic buoyancy and student's achievement are associated, the relationship is relatively modest. Aims We sought to determine whether another construct might link academic buoyancy and student's achievement. Based on prior theoretical and empirical work, we examined a sense of control as one possible linking mechanism. Sample The study analysed data from 2, 971 students attending 21 Australian high schools. Methods We conducted a cross‐lagged panel design as a first means of disentangling the relative salience of academic buoyancy, control, and achievement (Phase 1). Based upon these results, we proceeded with follow‐up analyses of an ordered process model linking the constructs over time (Phase 2). Results Findings showed that buoyancy and achievement were associated with control over time, but not with one another (Phase 1). In addition, control appeared to play a role in how buoyancy influenced achievement and that a cyclical process may operate among the three factors over time (Phase 2). Conclusion The findings suggest that control may play an important role in linking past experiences of academic buoyancy and achievement to subsequent academic buoyancy and achievement.